Meniscal Root Repair - John R. Matthews MD; Ryan W. Paul BS; Sommer Hammoud MD (SAGE Publishing, 2021)
Background: Meniscal root tears typically result from a hyperflexion/squatting injury or are in conjunction with ligamentous knee injury. Once a complete tear occurs, the meniscus is unable to convert axial loads to transverse hoop stresses which result in increased tibiofemoral contact pressure and osteoarthritis. The goal of a meniscal root repair is to anatomically reattach the meniscal root to the tibia plateau. Complete and partial healing occurs in over 93% of cases with retear rates ranging from 0% to 7%. Indications: We present a case of a highly active 21-year-old male collegiate soccer play that sustained a medial meniscal root tear after slipping on ice. Technique: An anatomic medial meniscal root repair was performed using a transtibial guide and 2 loop sutures tied over a button. Results: Full anatomic footprint coverage was able to be achieved intraoperatively and gentle range of motion from 0 to 90° of flexion did not result in gap formation. Discussion/Conclusion: Successful outcomes with full anatomic footprint coverage of the medial meniscal root can be achieved with 2-loop suture button configuration.